Discovery of HCV vaccine: Where do we stand? - Balakrishnan, Pachamuthu; Saravanan, Shanmugam; Vignesh, Ramachandran; Sivamalar, Sathasivam; Nallusamy, Duraisamy; Sankar, Sathish; Krithika, Chandrasekaran; Sridhar, Chitathoor; Raju, Sivadoss; Velu, Vijayakumar; Shankar, Esaki M. (Indian journal of medical microbiology, 2025)
Hepatitis C virus (HCV) is still a serious public health issue because it can cause cirrhosis, hepatocellular carcinoma (HCC), and chronic hepatitis. In almost 70 % of cases, HCV infection results in chronic persistence, which causes progressive liver disease over time. Though tremendous research has been done, even after achieving the cure, it has not brought out effective vaccines to prevent HCV transmission or a vaccine to prevent disease progression to liver diseases, including HCC. It has been reported that the challenges in the discovery of the HCV vaccine are primarily because the virus's genetic heterogeneity and very diversified nature are restricting the effectiveness of T-cell-based immunity as well as B-cell (neutralising antibody)-based immunity. Therefore, having an effective and robust HCV vaccine is essential to control and eliminate HCV from the world. The purpose of this review is to provide the current status of the protective role of T-cells and antibodies specific to HCV, with the available vaccination approaches, human clinical trials, and their outcomes. The development of HCV vaccines employs a variety of tactics to elicit host immune responses. Preventive and therapeutic vaccinations are the two main categories of HCV vaccines currently under research. Numerous HCV vaccine candidates have been assessed, with the majority focusing on humoral and/or cellular immunity using both animal models and human volunteers. Recombinant subunit vaccines, virus-like particles (VLPs), synthetic peptides, DNA vaccines, and viral vectors expressing different antigens are some of the current methods used to build a vaccine against HCV. Though the initial results were encouraging with several HCV vaccine candidates, most either failed to reach the next level of clinical evaluation.